Endodontic treatment of maxillary second molar with two roots: A case report - Dajana Nogo Živanović; Dragan Ivanović; Tanja Ivanović; Ivana Simić (Биомедицинска истраживања, 2020)
Introduction: The success of endodontic treatment depends on the adequate biomechanical preparation and obturation of the entire root canal system. The untreated or poorly debrided/obturated root canals are among the most frequent causes of endodontic treatment failure. The endodontic treatment of maxillary molar has the highest failure rates due to the complexity of their root canal anatomy. The aim of the study is to present the endodontic treatment of maxillary second molar with two roots and two canals. Case report. The clinical case report presents the endodontic treatment of maxillary second molar with two roots and two canals in a patient, aged 32 years. After the analysis of preoperative diagnostic radiograph, opening the pulp chamber and access cavity preparation, two canal orifices were localized. After the biomechanical preparation, root canals were obturated with the Gutta-percha points and sealer during the same visit. Conclusion: Although maxillary second molar most commonly varies in terms of the number of root canals in the buccal roots, less common variations in anatomical and morphological traits, such as the presence of two roots and two canals, should be considered during endodontic treatment.
Keywords: endodontic treatment; root canal morphology; maxillary second molar